The Internationalization of German Software-based Companies: Sustainable Growth Strategies for Small and Medium-sized Companies - Picot, A (Springer, 2015)
This book takes an in-depth look at the software industry as a major factor in future global economic performance. It explores how software-based companies are a significant factor behind economic growth and serve as important bridge builders between industries. Countries with a weak and underdeveloped software industry risk being left behind in the 21st century.